Basal ganglia infarction associated with HHV-6 infection. Issue 4 (1st April 1997) - Webb, David W; Bjornson, Bruce H; Sargent, Michael A; Hukin, Juliette; Thomas, Eva E
Abstract : A 6 year old boy presented with meningoencephalitis and was found to have serological evidence of acute human herpes virus-6 (HHV-6) infection. He did not develop symptomatic seizures or the rash of exanthum subitum (roseola). His course was marked by severe spastic quadriparesis associated with radiological evidence of basal ganglia infarction. HHV-6 infection should be considered in any child with acute meningoencephalitis.